Coalition of injustice? Bodies, business, and the biosphere in struggles against unwanted land uses. Issue 3 (3rd May 2016) - Kaup, Brent Z.; Casey, Daniel
ABSTRACT: Scholars of environmental injustice have pushed to see beyond the spatial distribution of environmental harms in studies of unwanted land uses. Building upon this work, this article examines how the complex geographies of environmental injustice play out in a coalition to prevent the construction of a coal-fired power plant in Surry County, Virginia. While spatially dispersed coalitions of negatively affected actors can strengthen efforts to prevent the construction of an unwanted land use, they can also perpetuate the environmental injustices surrounding it. To make this argument, particular attention is paid to the diverse reasons and ways differentially situated actors oppose an unwanted land use. It is demonstrated how the disparate concerns and differential tactics deployed by actors in coalitions against unwanted land uses are often embedded in and potentially contribute to longer histories of social injustice.